2016
DOI: 10.1111/jpm.12345
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of schizophrenia and coping styles in caregivers: comparison between India and Switzerland

Abstract: Introduction Scientific and theoretical framework showed that culture and health organization system influence perception of illnesses and thus also has an impact on the coping strategies used. Aim/question This cultural comparative study explores illness' perception and coping styles among the caregivers of people diagnosed with schizophrenia spectrum disorders in Mangalore, India, and Lausanne, Switzerland. Method The answers of 92 Swiss caregivers, using paper or electronic surveys depending on the particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 59 publications
0
13
0
1
Order By: Relevance
“…[8,10,11] Bu ailelerin karşılaşabileceği zorluklara yönelik genel bir farkındalık mevcut olsa da bakım vermeye ilişkin sorumluluklar göz önüne alındığında bu kişiler beklemedikleri duygusal, psikolojik, fiziksel ve ekonomik zorluklar yaşayabilmekte ve bu da ailenin işlevselliğinde bozulmalara yol açabilmektedir. [12][13][14][15][16][17] Pozitif veya negatif semptomların şiddeti; hastanede yatma, doktor kontrolüne gitme, ilaç tedavisi ve düşük işlevsellik şizofreni hastalarına yönelik bakım veren yükünü artıran faktörler arasındadır. Ancak şizofreni hastalarına bakım veren kişilerin yaşadığı bakım yükünü etkileyen en önemli problemler genel işlevsellikte ortaya çıkan sorunlar, günlük yaşam aktivitelerini yerine getirememe, sosyal işlevselliğin bozulması ve hastaların eğitim ve mesleki yaşamlarındaki karşılaştıkları zorluklardır.…”
unclassified
“…[8,10,11] Bu ailelerin karşılaşabileceği zorluklara yönelik genel bir farkındalık mevcut olsa da bakım vermeye ilişkin sorumluluklar göz önüne alındığında bu kişiler beklemedikleri duygusal, psikolojik, fiziksel ve ekonomik zorluklar yaşayabilmekte ve bu da ailenin işlevselliğinde bozulmalara yol açabilmektedir. [12][13][14][15][16][17] Pozitif veya negatif semptomların şiddeti; hastanede yatma, doktor kontrolüne gitme, ilaç tedavisi ve düşük işlevsellik şizofreni hastalarına yönelik bakım veren yükünü artıran faktörler arasındadır. Ancak şizofreni hastalarına bakım veren kişilerin yaşadığı bakım yükünü etkileyen en önemli problemler genel işlevsellikte ortaya çıkan sorunlar, günlük yaşam aktivitelerini yerine getirememe, sosyal işlevselliğin bozulması ve hastaların eğitim ve mesleki yaşamlarındaki karşılaştıkları zorluklardır.…”
unclassified
“…The findings of the study showed that out of all of the family members with schizophrenia, 46 % experienced a relapse at least one to three times and the others, more than three times. If repeated relapse continues in patients with schizophrenia, it can have negative consequences for the caregivers (Rexha, Jose, Golay, & Favrod, 2006). Recurrent schizophrenic patients exhibit uncontrollable behavior, such as being angry without cause, and suspicious excessive and unnatural behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Their study revealed the experiences of caring for children/adolescents with schizophrenia in the long-term; however, there is a lack of studies considering parents' experiences in the short-term. In addition, the experiences of individuals caring for patients with schizophrenia vary across different cultures, 18,19 and little is known about the challenges of parents in this situation in China. This study attempted to answer the questions "What are the challenges faced by parents caring for ESS children/adolescents in China?," and our assumption is that those challenges different from those faced by caregivers who care for children/adolescents with schizophrenia in the longterm and who in other cultures.…”
Section: Introductionmentioning
confidence: 99%